Waste burning in Kalipentung hamlet, Kalitirto, Berbah, Sleman - Munawaroh Inamatul; Sulistyawati; Aqmarina Nurma (BIO Web of Conferences)
Health development cannot be separated from early efforts to prevent the disease. This cannot be done only by the government but also by the community. To prevent disease early, community diagnosis can be an effective measure. The aim of this research is to carry out a community diagnosis to identify the main problems faced by the community, which are then used as evidence to determine strategies for solving these problems. This research was an observational study by conducting community diagnosis using a questionnaire to the community of RT 03 Kalipentung Hamlet in April-June 2022. A total of 30 families participated in this study, most of which had completed junior high school education. From the results of this study, it is known that many people still handle waste by burning, and it is feared that it will cause serious health problems such as worsening the respiratory tract. Based on the primary health priority in RT 03 Kalipentung Hamlet, namely handling waste by burning, an intervention was carried out with waste management education using leaflet media to increase public understanding regarding good and correct waste management.